POSITIVE INTERACTION IN AN INCLUSIVE EDUCATION: MANIFESTATION OF THE INTERNATIONAL CHILD DEVELOPMENT PROGRAMME (ICDP) - Farid Alamdar oglu Suleymanov (Russian State Vocational Pedagogical University, 2016)
Abstract. Kind relation between a child and caregiver (parent, teacher) is a critically vital point for psychological development of children. Better relations also contribute to the child's healthy growth and intellectual, social and emotional development. Fundamental caregiving skills function as particularly important contribution to the quality and effectiveness all caregiving. In order to facilitate full development of a child, it is important that the caregiver have a positive conception of the child. In other words, a caregiver should regard a child as a person with potential for development. From this perspective International Child Development Programme (ICDP) functions as a resource-based communication and mediation approach which trains caregiver to develop a positive conception of their children and gain wider and deeper insight and confidence about their responsibilities and roles. Based on the themes of ICDP, the current research studied the quality of positive interaction between teacher assistants (TA) and children with special needs (CSN) in an inclusive primary education in Azerbaijan. The findings suggest that some elements of ICDP approach exist in teacher-student interaction. However, these interaction patterns are unprofessional and need development through relevant in-service trainings. Methods. In this research a case study design of qualitative research was used to investigate teacher assistants' (TA) understanding of positive attitude and how they establish positive relations with the students with special needs whom they take care of. As for the research method, the case study will adopt triangulation, a multiple methods of data collection which will include interview and observation to extend confidence in its validity and improve the quality of the data and accuracy of the findings. Results. Comparative analyses of triangulation data demonstrate that TAs' performance within the context of teacher-student positive interaction lags behind their conception of positive interaction patterns. That is to say, TAs spoke confidently, although unprofessionally, of the elements of positive interactions but did not demonstrate the same fully in their behavior. As observation data signified, the main reason of this, is that TAs lack professional techniques and skills for establishing positive interaction patterns. Scientific novelty and practical significance. Scientific novelty of the study indicates that positive interaction between teachers and pupils appears as an important factor in terms of emotional and cognitive health of children. The current study underlined once more the lack of some important features of professionalism in the teaching activity of the participants involved in the research. Moreover, the result of the research signifies that ICDP themes do not manifest fully in teaching process which was the target of this research and neither in the teaching practices carried out based on traditional and conservative teaching strategies and consequently they need to be involved into relevant trainings.